2016
DOI: 10.1002/pat.3751
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based polymer nanocomposite membranes: a review

Abstract: Ever since the discovery of graphene, its potential has been predicted for a number of applications in various fields such as electronics, sensors, environmental decontamination techniques, separations and biomedicine to name a few. Among various such fields, the research in graphene-based nanocomposites membranes is still in its infancy as there is not a significant research published in this field so far. However, interestingly this field is registering an exponentially upward trend recently. This review art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(79 citation statements)
references
References 104 publications
(109 reference statements)
0
78
0
1
Order By: Relevance
“…The samples were then cooled to room temperature and heated once again to 180°C at 10°C min −1 . The degree of crystallinity, X c, of samples was determined by Xc()%=HfHcHf0×100, where ∆H f is the melting enthalpy, Hf0 is the melting enthalpy of pure crystalline PLA (100% crystalline polylactide = 93 J g −1 ), and ∆H c is the crystallization enthalpy …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were then cooled to room temperature and heated once again to 180°C at 10°C min −1 . The degree of crystallinity, X c, of samples was determined by Xc()%=HfHcHf0×100, where ∆H f is the melting enthalpy, Hf0 is the melting enthalpy of pure crystalline PLA (100% crystalline polylactide = 93 J g −1 ), and ∆H c is the crystallization enthalpy …”
Section: Methodsmentioning
confidence: 99%
“…Polylactic acid (PLA), a naturally occurring biodegradable polymer, has attracted significant attention owing to its biocompatibility and biomedical applications . PLA possesses superior optical, physical, mechanical, and barrier properties when compared with commercially available polymers .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, graphene nanosheets (GNSs) consisting of one‐atom thick two‐dimensional (2D) graphite layers have attracted considerable attention because of the excellent mechanical properties and high thermal stability . It has been reported that very low GNS content could significantly enhance the crystallization ability and improve the physical properties of polymers .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that heat treatment of semi-crystalline polymers has beneficial effects on mechanical properties and solvent resistance since this tends to enhance crystallinity. [22][23][24] Therefore, graphene nanoplatelets were selected as the filler material for this study (see also ref. Nanoplatelets and crystallites both work as impermeable barriers, and a diffusing molecule has to travel a longer, tortuous path around these obstacles.…”
Section: Introductionmentioning
confidence: 99%